DELAY OF REWARD AND THE LEARNING OF A SIZE PROBLEM BY NORMAL AND RETARDED CHILDREN. - Ross, Leonard E.; Hetherington, Mavis; Wray, Nancy P. (Child Development, 1965)
The performance of normal and moderately retarded children was compared on a size-discrimination problem under three delay-of-reward conditions (0, 12, and 18 sec) and with the chosen stimulus visible (V) or not visible (NV) during the delay period In the study 24 normal and 24 moderately retarded children, matched on MA, were run under 0, 12V, 12 NV, 18 V, and 18 NV conditions (total N = 240) The IQ factor was significant under both V and NV conditions, with retardates showing poorer performance Over all, delay was significant for the V condition but not for the NV condition (p < .10) Transposition test trials were given following learning.